Penyimpangan Nilai Moral dalam Lakon Rama Bargawa: Tinjauan Sosiologi Sastra - Atmaja, Mahendra; Sukisno, Sukisno (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
This study aims to identify and analyze the deviations in moral values depicted in the Rama Bargawa puppet play through a sociology of literature approach. The Rama Bargawa play was chosen because of its complexity in depicting the social and moral dynamics of society, especially related to the deviations committed by its characters. This study uses a qualitative description method with an embedded and case study research strategy, which focuses on the analysis of the puppeteer's dialogue in the Rama Bargawa play sourced from a YouTube video. The results of the study show that the Rama Bargawa play contains various deviations in moral values, such as infidelity, unwillingness to take responsibility, broken promises, anger, and murder. These deviations not only reflect individual conflicts, but also broader social and cultural conditions. Through a sociology of literature analysis, it is revealed that the immoral actions committed by the characters in the Rama Bargawa play, who are in fact educated and respected people, are a reflection of the dynamics of power, injustice, and norms that apply in society at that time. This study concludes that the play Rama Bargawa functions as a mirror that reflects social and cultural realities, and how deviations in moral values can be a representation of broader problems in a social context. A sociological analysis of literature on this play provides a deeper understanding of how literary works can be used to criticize and reflect on the conditions of society.